2005
DOI: 10.1007/s00415-005-0654-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for critical illness polyneuromyopathy

Abstract: Although numerous clinical, laboratory, and pharmacological variables have been reported as significant risk factors for critical illness polyneuromyopathy (CIPM), there is still no consensus on the aetiology of this condition. Objectives of the study were to assess the clinical and electrophysiological incidence and risk factors for CIPM.A cohort of critically ill patients was observed prospectively for a one-month period and the association between neuromuscular involvement and various potential risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
0
22

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(162 citation statements)
references
References 41 publications
2
134
0
22
Order By: Relevance
“…Eleven out of the 29 (38%) 25,28,29,32,[36][37][38][39][40][41][42] observational studies were graded of low quality, 17 out of 29 (59%) 12,[14][15][16]20,24,26,27,30,[43][44][45][46][47][48][49][50] as medium and one (3%) 51 as high quality. There were four RCTs included; two studies were deemed of low risk, 22,23 one unclear risk 8 and one with high risk 31 of bias.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…Eleven out of the 29 (38%) 25,28,29,32,[36][37][38][39][40][41][42] observational studies were graded of low quality, 17 out of 29 (59%) 12,[14][15][16]20,24,26,27,30,[43][44][45][46][47][48][49][50] as medium and one (3%) 51 as high quality. There were four RCTs included; two studies were deemed of low risk, 22,23 one unclear risk 8 and one with high risk 31 of bias.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…These studies, however, did not adjust for confounding variables that might associate with the development of NMD and, in fact, many of these same patients with ICU weakness had sepsis, multi-organ dysfunction (MOD), or organ rejection. Further prospective studies subsequently found no association between NMD and either steroids or neuromuscular blockade [9,10,24], although in one report corticosteroid administration was associated with NMD in multivariate analysis (OR 14.9, 95% CI 3.2-69.8, p <0.001) [21].…”
Section: Risk Factors For Acquired Neuromuscular Weaknessmentioning
confidence: 94%
“…Alternate terms include ICU-acquired paresis, critical illness neuromyopathy, and critical illness neuromuscular abnormalities. CIM has been reported in at least one third of ICU patients treated for status asthmaticus [8] and studies of critically ill patients suggest incidence rates between 12-35% [9][10][11][12]. Prospective studies suggest that CIP may occur in up to 50-70% of patients admitted to the ICU with a diagnosis of systemic inflammatory response syndrome (SIRS) [13][14][15].…”
Section: Incidence Of Acquired Neuromuscular Dysfunction In the Icumentioning
confidence: 99%
See 2 more Smart Citations